Berkshire encyclopedia of extreme sports - Booth, Douglas; Thorpe, Holly; Gale Group (Great Barrington, Mass. Berkshire Publishing Group, 2007)
Provides numerous articles written by sports experts and athletes that describe and explain extreme sports. Also includes biographies on leading athletes, essays on extreme sports venues, and articles on social issues.
List of entries -- Introduction -- Acknowledgments -- Reader's guide -- Contributors -- About the editors -- Disclaimer -- Entries -- Index.
Keywords: Extreme sports -- Encyclopedias; Athletes -- Biography; Electronic books